2022
DOI: 10.1111/echo.15470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitral valve transcatheter edge‐to‐edge repair on indices of left atrial performance in chronic mitral regurgitation

Abstract: Introduction: Effect of transcatheter edge-to-edge repair (TEER) using MitraClip in patients with mitral regurgitation (MR) on left atrial (LA) kinetic energy (LAKE), an index of LA work, and LA strain, a measure of LA performance, have not been well defined. Methods:Patients with chronic primary or secondary 3+ or 4+ MR were analyzed preand post-TEER using MitraClip. LAKE was determined by echocardiography using LA stroke volume and A-wave velocity. Peak atrial longitudinal strain (PALS), peak atrial strain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Improvement in other parameters, such as strain has been observed but little else has been described. 5 Dilation of the right atrium does often represent long-standing pressure and volume overload. It remains to be seen if the bi-atrial pathology corresponds with concomitant mitral and tricuspid regurgitation, simply pressure overload from singular left-sided lesions, concomitant atrial fibrillation, or just any combination of these issues.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in other parameters, such as strain has been observed but little else has been described. 5 Dilation of the right atrium does often represent long-standing pressure and volume overload. It remains to be seen if the bi-atrial pathology corresponds with concomitant mitral and tricuspid regurgitation, simply pressure overload from singular left-sided lesions, concomitant atrial fibrillation, or just any combination of these issues.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, unlike the electrophysiology literature, interventionalists have yet to demonstrate left atrial volume reduction or associated improved outcomes in mitral TEER. Improvement in other parameters, such as strain has been observed but little else has been described 5 …”
mentioning
confidence: 99%
“…The cessation of or reduction in regurgitant volume after intervention reduce left atrial extension and pressure; however, the improvement in left atrial function might depend on preoperative strain values [ 169 ]. Improvement in atrial function after transcatheter mitral valve repair (e.g., MitraClip implantation) is controversial [ 169 , 170 , 171 , 172 , 173 , 174 , 175 ]. Some study groups have found improvements in left atrial function after the transcatheter procedure; however, others have found no relevant change or even worsening [ 169 , 170 , 171 , 172 , 173 , 174 , 175 ].…”
Section: Valvular Heart Disease and Atrial Cardiomyopathymentioning
confidence: 99%
“…Improvement in atrial function after transcatheter mitral valve repair (e.g., MitraClip implantation) is controversial [ 169 , 170 , 171 , 172 , 173 , 174 , 175 ]. Some study groups have found improvements in left atrial function after the transcatheter procedure; however, others have found no relevant change or even worsening [ 169 , 170 , 171 , 172 , 173 , 174 , 175 ]. This might be due to the low study sample size and differences between study designs, including the etiology of mitral regurgitation, left ventricular function, the presence of atrial fibrillation, and the severity of residual mitral regurgitation after MitraClip implantation [ 169 , 170 , 171 , 172 , 173 , 174 , 175 ].…”
Section: Valvular Heart Disease and Atrial Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation